Isolated Hepatitis B Core Antibody Positivity and Long-Term Liver-Related Mortality in Korea: A Cohort Study. (6th September 2022) - Sohn, Won; Chang, Yoosoo; Cho, Yong Kyun; Hong, Yun Soo; Ryu, Seungho
Abstract : INTRODUCTION: Whether isolated hepatitis B core antibody (anti-HBc) positivity is a risk factor for long-term liver-related outcomes in hepatitis B virus (HBV)-endemic areas remains unclear. We aimed to investigate liver-related and liver cancer mortality of isolated anti-HBc positivity in Korean adults. METHODS: A cohort study comprised 609, 299 Korean adults who underwent hepatitis B serologic markers, as a part of health examination. Liver-related and liver cancer mortality were determined using the National Death Records. RESULTS: During a median follow-up of 9.0 years (interquartile range, 5.5–13.7 years), 554 liver-related deaths were identified (liver-related mortality, 9.6 cases per 10 5 person-years). The prevalence of isolated anti-HBc positivity was 3.8% (n = 23, 399) and was age-dependent. After adjustment for age, sex, and other confounders, hazard ratios (95% confidence interval) for liver-related mortality in isolated anti-HBc-positive and hepatitis B surface antigen–positive subjects compared with HBV-unexposed subjects were 1.69 (1.22–2.33) and 27.02 (21.45–34.04), respectively. These associations were pronounced in the analyses using liver cancer mortality as an outcome. Among isolated anti-HBc-positive patients, the risks of liver-related and liver cancer mortality were significantly higher in those with high fibrosis-4 scores compared with patients unexposed to HBV with the multivariable-adjusted hazard ratios (95% confidence interval) of 15.59 (9.21–26.37) and 72.66 (36.96–142.86), respectively. DISCUSSION: In this cohort of Korean adults, isolated anti-HBc positivity was associated with an increased risk of liver-related and liver cancer mortality, especially when accompanied by a high fibrosis score. Isolated anti-HBc positivity may be an independent risk factor for liver-related outcomes, especially in high-endemic areas.